If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 23 = 8(x + 6) Reorder the terms: 23 + 3x = 8(x + 6) Reorder the terms: 23 + 3x = 8(6 + x) 23 + 3x = (6 * 8 + x * 8) 23 + 3x = (48 + 8x) Solving 23 + 3x = 48 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 23 + 3x + -8x = 48 + 8x + -8x Combine like terms: 3x + -8x = -5x 23 + -5x = 48 + 8x + -8x Combine like terms: 8x + -8x = 0 23 + -5x = 48 + 0 23 + -5x = 48 Add '-23' to each side of the equation. 23 + -23 + -5x = 48 + -23 Combine like terms: 23 + -23 = 0 0 + -5x = 48 + -23 -5x = 48 + -23 Combine like terms: 48 + -23 = 25 -5x = 25 Divide each side by '-5'. x = -5 Simplifying x = -5
| 62.9296*x+64.9278*(1-x)=63.546 | | 11=8x+10-x+5 | | 5x+2=3(2x-4)+8 | | 4b=4b+33 | | (x-1)/(4x+7)=1/5 | | 12x+-12+23=56 | | 62.9296*x+64.9278*(100-x)=63.546 | | (2x^5+5x^4+25X^3+30x^2+45x+65)=0 | | solvex^4-9x^2+8=0 | | 67=8n+5 | | Z+y/5 | | 5-2x=-13-5x | | 2/5=a-4/6 | | 6-2(x+3)-x=-x-4(x+2) | | X=5(4x) | | -(3y+2)-(-2y-3)=-5 | | -1-8p=-10p-9 | | 7/m=3/m-2 | | 9y=2y^2+4 | | X/-2-14=-10 | | 3(4m+5)=3m-3 | | 21x^2-13x=-8 | | 2(x-1)/6=3x-5 | | -3(2x-1)=11x | | 6n+4=1n-11 | | -23-11= | | -3+12=13x-5-12x | | 7/9=p+1/3 | | 54+.09m=38+.13m | | 5x/x-1+1/x=6 | | 1/6y^2=y-3/2 | | 33x^2-37x+10=0 |